2017
DOI: 10.1016/j.ymben.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 promotes metabolic flexibility in response to energy stress

Abstract: The Liver Kinase B1 (LKB1) tumor suppressor acts as a metabolic energy sensor to regulate AMP-activated protein kinase (AMPK) signaling and is commonly mutated in various cancers, including non-small cell lung cancer (NSCLC). Tumor cells deficient in LKB1 may be uniquely sensitized to metabolic stresses, which may offer a therapeutic window in oncology. To address this question we have explored how functional LKB1 impacts the metabolism of NSCLC cells using 13C metabolic flux analysis. Isogenic NSCLC cells exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 52 publications
6
35
0
Order By: Relevance
“…Compared with LKB1 wild-type H441 cells, LKB1 mutant cells (H23, HCC44, and H1355) were much more sensitive to HBSS starvation-induced cell death (Fig. 7B), supporting the concept that loss of LKB1 leads to less plasticity in response to nutrient deprivation (Jeon et al 2012;Parker et al 2017). Furthermore, ATG7 knockdown not only inhibited cell proliferation of LKB1 mutant cells in nutrient-rich conditions ( Fig.…”
Section: Autophagy Supports Lkb1 Mutant Human Lung Cancer Cells To Susupporting
confidence: 59%
See 2 more Smart Citations
“…Compared with LKB1 wild-type H441 cells, LKB1 mutant cells (H23, HCC44, and H1355) were much more sensitive to HBSS starvation-induced cell death (Fig. 7B), supporting the concept that loss of LKB1 leads to less plasticity in response to nutrient deprivation (Jeon et al 2012;Parker et al 2017). Furthermore, ATG7 knockdown not only inhibited cell proliferation of LKB1 mutant cells in nutrient-rich conditions ( Fig.…”
Section: Autophagy Supports Lkb1 Mutant Human Lung Cancer Cells To Susupporting
confidence: 59%
“…Loss of Lkb1 causes Kras-driven lung tumors to escape adenoviral-Cre-mediated Atg7 deletion Loss of LKB1 promotes cell growth but also results in broad defects in metabolic control in response to nutrient deprivation and other types of metabolic stress (Jeon et al 2012;Parker et al 2017). To test the hypothesis that autophagy is required to compensate for LKB1 loss-induced decrease in metabolic plasticity for tumor growth, KL mice were crossed with Atg7 flox/flox mice possessing conditional deficiency in Atg7 (Komatsu et al 2005) to generate a cohort that was either Atg7 +/+ or Atg7 flox/flox .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of the crucial modulator of the correlation between HA and metabolic characteristics may help unravel the etiology of PCOS and offer innovative approaches to treat PCOS. LKB1 can modulate energy sensing and metabolism [32,33]. In our study, we found that excessive LKB1 expression suppressed the generation of androgen in TCs and promoted the generation of estrogen in GCs, while the knockdown of LKB1 promoted the generation of androgen and inhibited the generation of estrogen.…”
Section: Discussionsupporting
confidence: 50%
“…64 GC-MS analysis was carried out and analyzed as described. 65 In brief, dried, extracted metabolites were derivatized using a MOX-tBDMCS method and analyzed by GC-MS using a DB-35MS column (30 m x 0.25 mm i.d., 0.25 µm) in an Agilent 7890B gas chromatograph interfaced with a 5977B mass spectrometer. Metabolites were identified by unique fragments and retention time in comparison to known standards.…”
Section: Metabolite Profiling: Steady-state and Labeling Experimentsmentioning
confidence: 99%